Annual direct and indirect costs attributable to nocturia in Germany, Sweden, and the UK - Weidlich, Diana (Eur J Health Econ, 2016)
OBJECTIVE: Our aim was to estimate the prevalence-based cost of illness imposed by nocturia (≥2 nocturnal voids per night) in Germany, Sweden, and the UK in an average year. METHODS: Information obtained from a systematic review of published literature and clinicians was used to construct an algorithm depicting the management of nocturia in these three countries. This enabled an estimation of (1) annual levels of healthcare resource use, (2) annual cost of healthcare resource use, and (3) annual societal cost arising from presenteeism and absenteeism attributable to nocturia in each country. RESULTS: In an average year, there are an estimated 12.5, 1.2, and 8.6 million patients ≥20 years of age with nocturia in Germany, Sweden, and the UK, respectively. In an average year in each country, respectively, these patients were estimated to have 13.8, 1.4, and 10.0 million visits to a family practitioner or specialist, ~91,000, 9000, and 63,000 hospital admissions attributable to nocturia and 216,000, 19,000, and 130,000 subjects were estimated to incur a fracture resulting from nocturia. The annual direct cost of healthcare resource use attributable to managing nocturia was estimated to be approximately €2.32 billion in Germany, 5.11 billion kr (€0.54 billion) in Sweden, and £1.35 billion (€1.77 billion) in the UK. The annual indirect societal cost arising from both presenteeism and absenteeism was estimated to be approximately €20.76 billion in Germany and 19.65 billion kr (€2.10 billion) in Sweden. In addition, in the UK, the annual indirect cost due to absenteeism was an estimated £4.32 billion (€5.64 billion). CONCLUSIONS: Nocturia appears to impose a substantial socioeconomic burden in all three countries. Clinical and economic benefits could accrue from an increased awareness of the impact that nocturia imposes on patients, health services, and society as a whole.